Effects of metformin on arterial elasticity and pro-inflammatory markers in black diabetes patients - Tsakani L. Rasakanya; Elzbieta Osuch (AOSIS, 2024)
Background: Pro-inflammatory markers are linked with the development and progression of type 2 diabetes mellitus and arterial stiffening. Pulse Wave Velocity (PWV) and Augmentation Index (Aix) are non-invasive standard markers of arterial elasticity and predictors of cardiovascular mortality and morbidity. Aim: To investigate the effects of metformin alone and in combination with glimepiride on arterial elasticity, pro-inflammatory cytokines in black type 2 diabetes mellitus patients. Settings: Participants were enrolled from Sefako Makgatho Health Sciences University community, Gauteng, South Africa. Methods: PWV and Aix were measured using the AtCor SphygmoCor® system (AtCor Medical, Inc., Sydney, Australia). Cytokines levels were measured using Multiplexing with Bio-Plex Pro™ human inflammation panel I assay. Treatment naïve type 2 diabetes participants were divided into two groups: metformin (M) (n = 10) and metformin glimepiride (MS) (n = 14). The study participants were followed up at 4 and 8 months after treatment initiation. Results: In the M and MS, IL-1β increased significantly at four months (58.19 ± 0.03 pg/ml, 58.35 ± 0.30 pg/ml) when compared to baseline (33.05 ± 18.56 pg/ml, 34.79 ± 18.77 pg/ml) then decreased significantly at eight months (29.25 ± 11.64 pg/ml, 32.54 ± 14.26 pg/ml) when compared to four months (58.19 ± 0.03 pg/ml, 58.35 ± 0.3 pg/ml) (p  0.05). There were no significant changes in PWV, Aix, IL-1ra, IL-2, IL-6, IL-8, TNF-α and hs-CRP levels at both treatment intervals. Conclusion: Metformin alone or in combination with glimepiride did not improve arterial elasticity and did not reduce pro-inflammatory cytokines levels in T2DM black South African patients. Contribution: The context-based knowledge generated by the current study is expected to enhance the continuum of care for T2DM patients.